2022
DOI: 10.1186/s12870-022-03638-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biogenic silver and iron nanoparticles on soybean seedlings (Glycine max)

Abstract: Background Biogenic metallic nanoparticles have been emerging as a promising alternative for the control of phytopathogens and as nanofertilizers. In this way, it is essential to investigate the possible impacts of these new nanomaterials on plants. In this study, the effects of soil contamination with biogenic silver (AgNPs) and iron (FeNPs) with known antifungal potential were investigated on morphological, physiological and biochemical parameters of soybean seedlings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 52 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…181,[186][187][188] In general, compared with the aboveground parts of plants, the oxidative damage of roots exposed to MNPs is more significant because of the direct contact between roots and MNPs, which is characterized by a significant increase in H 2 O 2 and conjugated dienes. 189 In a hydroponic experiment, it was found that the content of malondialdehyde (MDA) increased as the concentration of Al 2 O 3 and CuO NPs increased, and reached the highest at 2000 mg L −1 , which was 25.8 ± 2.3 and 40.8 ± 3 (nM × 10 2 ) per g FW, respectively. The subsequent DCF fluorescence labeling results showed that higher concentrations of Al 2 O 3 and CuO NPs (200 and 2000 mg L −1 ) induced a sharp increase in DCF fluorescence in roots, indicating the formation of ROS in roots.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…181,[186][187][188] In general, compared with the aboveground parts of plants, the oxidative damage of roots exposed to MNPs is more significant because of the direct contact between roots and MNPs, which is characterized by a significant increase in H 2 O 2 and conjugated dienes. 189 In a hydroponic experiment, it was found that the content of malondialdehyde (MDA) increased as the concentration of Al 2 O 3 and CuO NPs increased, and reached the highest at 2000 mg L −1 , which was 25.8 ± 2.3 and 40.8 ± 3 (nM × 10 2 ) per g FW, respectively. The subsequent DCF fluorescence labeling results showed that higher concentrations of Al 2 O 3 and CuO NPs (200 and 2000 mg L −1 ) induced a sharp increase in DCF fluorescence in roots, indicating the formation of ROS in roots.…”
Section: Oxidative Stressmentioning
confidence: 99%